Development of Highly Sensitive Fluorescent Sensors for Separation-Free Detection and Quantitation Systems of Pepsin Enzyme Applying a Structure-Guided Approach - Aya M. Mostafa; Stephen J. Barton; Stephen P. Wren; James Barker (Biosensors, 2024)
Two fluorescent molecularly imprinted polymers (MIPs) were developed for pepsin enzyme utilising fluorescein and rhodamine b. The main difference between both dyes is the presence of two (diethylamino) groups in the structure of rhodamine b. Consequently, we wanted to investigate the effect of these functional groups on the selectivity and sensitivity of the resulting MIPs. Therefore, two silica-based MIPs for pepsin enzyme were developed using 3-aminopropyltriethoxysilane as a functional monomer and tetraethyl orthosilicate as a crosslinker to achieve a one-pot synthesis. Results of our study revealed that rhodamine b dyed MIPs (RMIPs) showed stronger binding, indicated by a higher binding capacity value of 256 mg g−1 compared to 217 mg g−1 for fluorescein dyed MIPs (FMIPs). Moreover, RMIPs showed superior sensitivity in the detection and quantitation of pepsin with a linear range from 0.28 to 42.85 µmol L−1 and a limit of detection (LOD) as low as 0.11 µmol L−1. In contrast, FMIPs covered a narrower range from 0.71 to 35.71 µmol L−1, and the LOD value reached 0.34 µmol L−1, which is three times less sensitive than RMIPs. Finally, the developed FMIPs and RMIPs were applied to a separation-free quantification system for pepsin in saliva samples without interference from any cross-reactors.